Nature-Based Environments for Health, Well-Being and Performance: A Hypothesis on Sport and Exercise Behavior - Henrique Brito; Henrique Lopes; Eric Brymer; Duarte Araújo (Sports, 2026)
A fundamental concern for coaches and sport practitioners is developing athlete performance while preserving health and well-being. An emerging topic is that performing in nature-based environments may have more benefits than performing in typical built/indoor environments. However, to understand athlete performance and well-being, it is essential to recognize how performers accommodate (adapt) skills and resources under environmental constraints in pursuit of sport and exercise task goals. This article presents a narrative review to support a hypothesis on the sustained benefits of performing in nature-based environments, with health and well-being as necessary aspects for performance, grounded in the ecological dynamics theoretical framework. We start by discussing: (i) performance in nature-based and indoor environments underpinned by affordance perception; (ii) evidence for the role of nature-based environmental constraints on movement and psychological aspects; (iii) the hypothesis that prolonged engagement with nature-based environments during sport and exercise may promote adaptive skill development, health, and well-being, and may facilitate the transfer of these adaptations to performance in built indoor competitive settings; (iv) the distinct lived experiences (e.g., emotion, well-being) that emerge from exercising in nature-based and built indoor environments; and (v) suggestions on how to include nature-based constraints on sport and exercise training, and future research considerations. Overall, the reviewed theoretical and empirical evidence provides a rationale for the hypothesis that prolonged engagement with nature-based environments during sport and exercise may promote adaptive skill development, health, and well-being, with potential transfer of these adaptations to performance in built indoor settings. Future longitudinal and experimental studies are required to test this hypothesis and determine whether, and under what conditions, these proposed adaptations transfer to performance in built indoor sport settings.